Multisystemic therapy for antisocial behavior in children and adolescents Malaysia - Ng, Haw Kuen; Wan Jaafar, Wan Marzuki (Malaysia Association of Research and Education for Educators, 2017)
According to statistics from the Department of Social Welfare (2015), a total of 4669 children between the ages of 10-21 were involved in crimes such as property-related criminal cases, minor offence act, infringement of supervision terms, drugs, gambling, weapons or firearms, traffic offences, escaping from approved schools and others. Various efforts have been put in to reduce the rate of involvement in crime amongst youths. However, statistics from the Department of Social Welfare showed that the number of children involved in crime was still very high – from 2009 to 2015, there were 35, 300 children, or an average of 5042 children a year, involved in crime. A lot of investments have gone into funding the cost for treatment and for institutions to resolve children criminal cases, but till today, we have not seen satisfactory results in reducing children’s involvement in crimes, in fact, the number of children involved in crimes has gone up as compared to the past. Despite the many measures taken to tackle this issue, what we are facing right now is the failure to break the vicious cycle when these children return to a troubled environment. For three decades, studies have shown that multisystemic therapy, which places serious juvenile offenders in the community with intensive intervention, has a significant effect in reducing their involvement in heavy crimes. According to Borduin et al. (1995), groups of delinquent youths were treated with multisystemic therapy or individual therapy after four years, and as a result, the youths who underwent the multisystemic therapy recorded significantly lower recurrence rate in perpetrating crimes.